Service Learning in Building an Attitude of Religious Moderation in Pesantren - Hasan, Moch. Sya'roni; Azizah, Mar'atul; Rozaq, Abd (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This article aims to describe the application of Service Learning learning in the formation of religious moderation in the Darussalam Pare Kediri Pondok Pesantren. A qualitative approach with the design of case studies is used to understand the impact of the application of this learning in developing a moderate attitude and a balanced religious understanding over the centuries. The research participants consisted of the centers involved in the Service Learning program and the educators who planned and oversaw its implementation. Data was collected through in-depth interviews with centers, participatory observations of learning activities, and analysis of program-related documents. Data credibility is strengthened through the triangulation of data sources and the verification of findings with respondents. Data portability is observed through an in-depth description of the training context. Data confirmability is emphasized by using direct quotes from the original data to support interpretation. The result of this research is to reveal the application of service learning capable of providing a real experience to the center in serving the community, understanding social reality, and connecting it with religious values. This research contributes to understanding how the application of Service Learning learning can help shape religious moderation among the clergy. These findings provide insight into the effectiveness of this approach in integrating religious understanding with real-life experiences in society.